2023
DOI: 10.1021/acs.cgd.3c00507
|View full text |Cite
|
Sign up to set email alerts
|

First Finding of High-Pressure Modifications of Na2CO3 and K2CO3 with sp3-Hybridized Carbon Atoms

Pavel N. Gavryushkin,
Nursultan E. Sagatov,
Dinara N. Sagatova
et al.

Abstract: The transition from structures with classical [CO 3 ] triangles to structures with [CO 4 ] tetrahedra, corresponding to the transition from sp 2 to sp 3 hybridization of carbon atoms, is quite well established for alkaline earth carbonates CaCO 3 and MgCO 3 . Here, using a crystal structure prediction technique, we show that alkali carbonates Na 2 CO 3 and K 2 CO 3 follow the same trend. Both compounds form isostructural sp 3 -hybridized phases, Na 2 CO 3 −C2/m and K 2 CO 3 −C2/m, which became thermodynamical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Previous studies of the behavior of alkaline-earth and alkali metal carbonates at high pressures have revealed several unexpected crystal chemical features. The high-pressure modifications of calcium, 12,37 magnesium, 12,13,38 sodium and potassium 14 carbonates contain carbon atoms in tetrahedral coordination. Moreover, it was shown that [CO 4 ] tetrahedra in these structures polymerize.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of the behavior of alkaline-earth and alkali metal carbonates at high pressures have revealed several unexpected crystal chemical features. The high-pressure modifications of calcium, 12,37 magnesium, 12,13,38 sodium and potassium 14 carbonates contain carbon atoms in tetrahedral coordination. Moreover, it was shown that [CO 4 ] tetrahedra in these structures polymerize.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the case of CaCO 3 , the structure with sp 3 -hybridyzed carbons occurs above 75 GPa, 12 while in the case of MgCO 3 , it occurs above 80 GPa 12,13 and in the case of Na 2 CO 3 and K 2 CO 3 , it appears above 100 GPa. 14 However, in some cases, such as SrCO 3 , 15 BaCO 3 15 and Li 2 CO 3 , 14 carbon remains in the sp 2 -hybridized state and [CO 4 ] tetrahedra are not observed up to 200 GPa. The present study aims to investigate whether the transition of carbon atoms to the sp 3 -hybridized state will be observed in the case of lead carbonate in the unexplored high-pressure region.…”
Section: Introductionmentioning
confidence: 99%